2009
DOI: 10.1016/j.jacc.2009.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Depression After Coronary Artery Disease Is Associated With Heart Failure

Abstract: Depression diagnosis was shown to be associated with an increased incidence of HF after CAD diagnosis, regardless of ADM treatment. This finding suggests the need to further study the effect of depression on HF risk among CAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 42 publications
5
42
0
3
Order By: Relevance
“…These findings were in line with those studies that have shown that individuals who experience negative emotions, such as depression, were at an increased risk of CAD (12,25,26). In a cohort of 7,709 patients with confirmed CAD but without a diagnosis of heart failure or depression, a subsequent diagnosis of depression was associated with 50% increase in the risk of heart failure (14). The Nurses' Health Study analysis also suggested that antidepressant use tripled the risk of sudden cardiac death in healthy women (15).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings were in line with those studies that have shown that individuals who experience negative emotions, such as depression, were at an increased risk of CAD (12,25,26). In a cohort of 7,709 patients with confirmed CAD but without a diagnosis of heart failure or depression, a subsequent diagnosis of depression was associated with 50% increase in the risk of heart failure (14). The Nurses' Health Study analysis also suggested that antidepressant use tripled the risk of sudden cardiac death in healthy women (15).…”
Section: Discussionsupporting
confidence: 91%
“…Despite availability of strong evidence on the link between depression and outcomes among patients with heart disease, the effect of depression on cardiovascular disease in general population is still not clear (12). Some (13)(14)(15), but not all (14,16) studies have shown positive results. For instance, a prospective cohort of 136,293 community-dwelling postmenopausal women revealed that new antidepressant use was not significantly associated with increased incidence of CAD (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with post-MI depression have a 1.6-to 2.7-fold increased risk of new cardiac events, cardiac mortality, and all-cause mortality within 24 months. 7 They also have an increased rate of subsequent heart failure, 8 hospital readmissions, 9 and overall increased healthcare resource utilization. 9 There have been several biological mechanisms by which depression may be related to coronary artery disease.…”
Section: Epression Is Prevalent Among Patients With Coronarymentioning
confidence: 99%
“…However, if any differences were found in recovery between the groups, the result would indicate new topics for further research. Health care professionals have recognized the necessity of interventions in general after MI [5,7] and for concentrating on anxiety and depression, which have strong negative effects on recovery after MI [8] .…”
mentioning
confidence: 99%